Existence and stability solutions of nonlinear stochastic functional partial integrodifferential equations with infinite delay. (2016) - Parthasarathy, Chinnasamy; Arjunan, M. Mallika; Vinodkumar, A.
In this paper, we are focused upon the results on existence, uniqueness and stability of mild solution for stochastic functional integrodifferential equations with non-Lipschitz condition. The theory of resolvent operator is utilised to exhibit the existence of these mild solutions. The results are obtained by using the method of successive approximation and Bihari's inequality. Finally, an example is provided for demonstration.